Solar activity and air-sea interactions in the North Atlantic drive multidecadal to centennial-scale hydroclimate variability in arid Central Asia during the Mid-Late Holocene - Xiang Mi; Fangyuan Lin; Ashish Sinha; Dianbing Liu; Huiru Tang; Lvfan Chen; Xu Lin; Qiong Zhang; Rustam Orozbaev; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Blood metal(loid)s, haemoglobin and goitre in pregnant women from the mercury-exposed and non-exposed environment (Aidarken area vs Kara-Suu area; Kyrgyz Republic) - Veronika Tursunova; Janja Snoj Tratnik; Rustam Tuhvatshin; Darja Mazej; Zhanibek Muratov; Rakhima Azhimamatova; Mohd Faizan Siddiqui; Anja Stajnko; Zdenka Šlejkovec; Peter Stegnar; Milena Horvat; Ingrid Falnoga (Environmental Research, 2025)

Kinetically accelerated sodium storage in Na3V1.7Fe0.3(PO4)3 enabled by activation of V4+/V5+ redox couples, oxygen vacancies and carbon composite engineering - Zhenchao Bai; Rui Wang; Quan Zong; Lijing Yan; Chengbin Jin; Da Chen; Mukhammadjon Adilov; Rustam Ashurov; Khatam Ashurov; Qiaoling Kang (Chemical Engineering Journal, 2025)

Leveraging Vegetation Indices and Random Forest for Soil Nutrient Monitoring in Winter Wheat - Shukhrat Shokirov; Ilhom Abdurahmanov; Zokhid Mamatkulov; Zoir Abdurahmanov; Doniyor Zarifboev; Rustam Oymatov; Zoltán Kovács; Judit Csabai; Ye Shiping; Obid Khakberdiev (Journal of the Indian Society of Remote Sensing, 2025)

Phosphorylated Derivatives of Quaternary Ammonium Salts: Synthesis, X-Ray Crystal Structure, Antimicrobial Activity and Ecotoxicity - Rustam R. Davletshin; Polina A. Kuryntseva; Aidar M. Gayneev; Gulnaz Sh. Galieva; Svetlana Yu. Selivanovskaya; Natal’ya V. Davletshina; Kamil A. Ivshin; Daut R. Islamov (Current Microbiology, 2025)

Integrated study of the deformed phosphorite dolomite of the Early Cambrian Sirban formation in the Lesser Himalayas, Pakistan - Khawaja Umair Majeed; Muhammad Saleem Mughal; Xijuan Tan; Sara Criniti; Massimo Civitelli; Muhammad Rustam Khan; Shoukat Hussain Khan; Salvatore Critelli (Acta Geochimica, 2025)

Synthesis of NiO/mesoporous aluminosilicate nanoparticles using natural template for green diesel production: the effect of Si/Al ratio - Stella Jovita; Nada Nadhifah; Riki Subagyo; Rustam Tamim; Eka Putra Ramdhani; Holilah Holilah; Nurul Asikin-Mijan; Hasliza Bahruji; Reva Edra Nugraha; Aishah Abdul Jalil; Suprapto Suprapto; Didik Prasetyoko (Biomass and Bioenergy, 2025)

Controlled electrochemical design of activated carbon surface chemistry: Enhanced copper recovery using functionalized walnut shell-derived sorbents - Dinara Abduakhytova; Saken Abdimomyn; Azhar Atchabarova; Mojtaba Mirzaeian; Rustam Tokpayev; Askar Mukanov; Graziella Liana Turdean; Fyodor Malchik; Mikhail Nauryzbayev (Journal of Water Process Engineering, 2025)

Variations in Central Asian dust activity and potential driving mechanisms over the past 80 kyr - Haoru Wei; Yougui Song; Yanping Wang; Mingyu Zhang; Hamid Gholami; Shugang Kang; Yue Li; Shukhrat Shukurov; Nosir Shukurov; Rustam Orozbaev (Gondwana Research, 2025)

The impact of government incentive strategies on household pharmaceutical waste recycling: A system dynamics approach - Chang-Yi Liu; Qian Yang; Zhi Liu; Adeela Rustam (Waste Management, 2025)

Geophysical Study of Crustal Deformation Using Gravity Data: Muzaffarabad and Adjoining Regions in Azad Jammu and Kashmir - Arooj Zulqranan; Michal Šprlák; Muhammad Rustam Khan; Fahad Hameed (Pure and Applied Geophysics, 2025)

Age and Petrogenesis of the newly Discovered Early Permian Granite in the Kumtor Gold Field, Kyrgyz Tien-Shan - Kyiazbek Asilbekov; Rustam Orozbaev; Etienne Skrzypek; Christoph Hauzenberger; Elena Ivleva; Daniela Gallhofer; Jian-Feng Gao; Nikolay Pak; Anatoliy Shevkunov; Anatoliy Bashkirov; Aizat Zhaanbaeva (Journal of Earth Science, 2025)

Ion exchange membranes in environmental applications: Comprehensive review - Yokubjon Bozorov; Khait Turaev; Rustam Alikulov; Masud Karimov; Bakhriddin Muminov; Elyor Berdimurodov; Ilyos Eliboev; Muslum Demir; Adeyinka Sikiru Yusuff; Natarajan Elangovan (Chemosphere, 2025)

Dual-grating smart window with vertically distributed transmittance to optimize indoor daylight distribution and solar heat gain - Rustam Zakirullin (Energy and Buildings, 2025)

Biogeochemistry and the environment - Rita Da Costa Pinto; Hilarius Donatus Hun; Hermania Em Wogo; Arie Purnomo Aji; Ari Yanda Rustam (International Geology Review, 2025)

Adaptation of global primary production model to the Greenland Sea conditions: parameterization and monitoring for 1998-2022 - Aleksandra Cherkasheva; Rustam Manurov; Piotr Kowalczuk; Alexandra N. Loginova; Monika Zabłocka; Astrid Bracher (Frontiers in Marine Science, 2025)
Phytoplankton are responsible for releasing half of the world’s oxygen and for removing large amounts of carbon dioxide from surface waters. Despite many studies on the topic conducted in the past decades, we are still far from a good understanding of ongoing rapid changes in the Arctic Ocean and how they will affect phytoplankton and the whole ecosystem. An example is the difference in net primary production modelling estimates, which differ twice globally and fifty times when only the Arctic region is considered. Here, we aim to improve the quality of Greenland Sea primary production estimates, by testing different versions of primary production model against in situ data and then calculating regional estimates and trends for 1998-2022 for those performing best. As a baseline, we chose the commonly used global primary production model and tested it with different combinations of empirical relationships and input data. Local empirical relationships were taken from measurements by the literature and derived from the unpublished data of Institute of Oceanology of Polish Academy of Sciences across the Fram Strait. For validation, we took historical net primary production 14 C data from literature and added to it our own gross primary production O 2 measurements. Field data showed good agreement between primary production measured with 14 C and O 2 evolution methods. From all the model setups, those including local chlorophyll a profile and local absorption spectrum best reproduced in situ data. Our modelled regional annual primary production estimates are equal to 346 TgC/year for the Nordic Seas region and 342 TgC/year for the Greenland Sea sector of the Arctic defined as 45°W-15°E, 66°33′N-90°N. These values are higher than those previously reported. Monthly values show a seasonal cycle with less monthly variability than previously reported. No significant increase or decrease in primary production was observed when studying regionally averaged trends. The accuracy of the selected here model setups to reproduce the field data in terms of Root Mean Square Difference is better than in the related Arctic studies. The improved primary production estimates strengthen researchers’ ability to assess carbon flux and understand biogeochemical processes in the Greenland Sea.